2016
DOI: 10.1007/s40090-016-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Process standardization and kinetics of ethanol driven biodiesel production by transesterification of ricebran oil

Abstract: In this study, trans-esterification of rice bran oil employing a heterogeneous catalyst like CaO has been conducted in a batch reactor with ethanol. The optimal set of various critical reaction parameters are found to be temperature of 70°C, reactant molar ratio 9:1, agitation speed of 600 rpm, catalyst mount of 3 wt % to maximize the biodiesel yield. For the heterogeneous system possibly influenced by reaction and pore diffusion, the controlling regime has been found based on the experimental data and well es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The matching of pH is an indication of the removal of all the impurities. The dehydration is carried out and the biodiesel is blended with n-butanol and diesel fuel for 30 minutes in a stirrer (Asokan et al 2019;Chhabra et al 2017;Sreedhar et al 2016). The percentage of biodiesel yield is calculated by using equation (1) (Arun et al 2018).…”
Section: Synthesis Of Biodiesel Blendsmentioning
confidence: 99%
“…The matching of pH is an indication of the removal of all the impurities. The dehydration is carried out and the biodiesel is blended with n-butanol and diesel fuel for 30 minutes in a stirrer (Asokan et al 2019;Chhabra et al 2017;Sreedhar et al 2016). The percentage of biodiesel yield is calculated by using equation (1) (Arun et al 2018).…”
Section: Synthesis Of Biodiesel Blendsmentioning
confidence: 99%
“…The authors reported the use of methanol as the reaction alcohol. Hoang et al [87] reviewed the rice bran oil biodiesel as a promising renewable alternative fuel to diesel, reporting only one study in the literature that uses ethanol as chain alcohol [88]. The authors used CaO as catalyst.…”
Section: Rice Bran Vegetable Oilmentioning
confidence: 99%
“…This enhancescarbon emissions, engenders environmental and human health concerns, as well as promoting ozone layer depletion and climate change (Banik et al, 2018). Consequent upon the aforementioned, attention is being directed to renewable energy resources in anticipation to the exhaustibility of fossil fuel reserves and the growing environmental concerns (Sreedhar and Yandapalli, 2016). Biodiesels are bio-based diesels, described as the best alternative fuels for diesel engines, are environmentally friendly, biodegradable, with higher energy efficiencies, and essentially non acidic (Igbumet al, 2012).…”
mentioning
confidence: 99%